EFEKTIVITAS MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE AND SHARE) & PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR RANAH KOGNITIF DAN KETERAMPILAN GENERIK SAINS PESERTA DIDIK KELAS - Amiruddin Takda; Sarman Sarman; Suritno Fayanto; Ahmad Salido; Meryana Benly (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to obtain data and practical information about the effectiveness and efficiency of the SSCS model and PBL model on learning outcomes of the cognitive sphere and generic science skills of Class X Students of SMAN 4 Kendari. This research is quasi-experimental with a quantitative descriptive form that uses two classes to be used as research objects without a control class. The sample was taken by purposive random sampling technique, class X MIA8 and class X MIA9 study with SSCS model and class X MIA2 and class X MIA5 study with PBL model. Research data is obtained through 1) Observation of learning and science generic skills; 2) LOC and KGS tests in multiple-choice, and 3) Documentation. Data were analyzed using Microsoft Excel and SPSS 16.0 at α = 0.05. The results of data analysis show: 1) The SSCS and PBL model show relative effectiveness 30,30% for the LOC and 116,29% for the SGS; 2) the SSCS shows the efficiency of 85,04% for the LOC and 20,3% for the SGS; while the PBL shows the efficiency of 67,6% % for the LOC and 42,3% for the SGS; 3) There is a significant difference in the average scores of the LOC of learners who are studying with the SSCS model and the PBL model; 4) There is a significant difference in the average scores of the SGS of learners who are studying with the SSCS model and the PBL model; 5) There is a significant difference in the mean value of N-gain LOC learners who are studying with the SSCS model and the PBL model, and 6) There was a significant difference in the mean value of N-gain SGS learners who studied with the SSCS model and the PBL model. The conclusion: The PBL model provides relatively better effectiveness than the SSCS model of HBK and KGS. Therefore, it is recommended to physics teachers in schools use SSCS models and PBL models on materials that require labs to improve the knowledge and skills of learners